The Assessment Of Fire Risk Rating Based On Uniform Building By-Law (Ubbl) For Buildings In Usm Engineering Campus - Hadi, Muhammad Muhaimin Azhad Noor (Universiti Sains Malaysia, 2022)
A fire risk assessment is a systematic examination of work activities and workplace poses a fire hazard to humans. A fire risk assessment can assist reduce or avoiding fires, safeguarding property and personnel, and identifying and controlling workplace dangers. Commonly fire risk assessment is done by using a checklist and giving the result of lacking criteria. To make fire risk assessment more efficient and functional, the compliance rate is being used to make a fire risk assessment more efficient. The purpose of this study is to develop the weightage scale for the passive and active criteria of UBBL and to analyse the compliance rate of the selected buildings in the Engineering Campus. In this study, fire risk assessment will be done in 7 buildings of the USM Engineering campus which are the Library, School of Civil Engineering, Laboratory Civil Engineering, School of Chemical Engineering, School of Mechanical Engineering, School of Material and Mineral Resources, and Hostel SH5. The weightage that has been used in this project is by referring earlier study which are solely for active and passive protection systems and the highest score weightage for active and passive are 7 and 3 respectively. The compliance rate for active and passive protection systems was achieved for every building that has been chosen. The greatest compliance rate for active and passive is Library which is 6.5877 and 2.172 correspondingly due to all the criteria has the highest score. Meanwhile, the lowest compliance rate for passive was the School of Mechanical Engineering which is 4.334 due to have highest distance for travel distance. The lowest compliance rate for active was Laboratory Civil which is 1.8072 due to the hose reel is not comply with the UBBL. Therefore, the compliance rate may help compared the fire risk assessment and can know the safety factor.